Synthesis and Characterization of Heterobinuclear Cadmium-Tungsten Complexes of Dithiocarbamates - Sundaram, R.; Nagaraja, K.S. (Asian Journal of Chemistry, 2016)
The heterobinuclear complexes [CdWO2(L)3(H2O2)] (L = diethyldithiocarbarnate, 4-morpholinyldithiocarbarnate, 1-piperidinyldithiocarbarnate) were prepared by the interaction of cadmium tungstate with the respective ligands in aqueous DMF. The magnetic moment (1.7 BM) and EPR studies suggested the presence of tungsten in the pentavalent state. The IR spectral bands suggested the presence of n(W=O) (900 cm-1) and n(Cd–O–W) (790 cm-1) and bidentate dithiocarbarnate ligands (1500 and 960 cm-1) in the molecule. The IR and thermal decomposition studies confirmed the presence of coordinated water molecules. The 1H NMR chemical shifts indicated non-identical environment of protons coming closer due to rigidity in rotation around C–N bond of dithiocarbarnate ligand and coordination to the heterometal atoms. The mass spectral data showed 16 lines at m/z 808-824 and subsequent peaks correspond to the fragmentation of water and dithiocarbarnate ligands in steps from the complex. The proposed structure consists of a tetrahedral cadmium(II) and octahedral tungsten(V) bridged by an oxo group.